Topical gentamicin 0.1% promotes collagen 7 expression in recessive dystrophic epidermolysis bullosa - Rahul Mahajan; Seema Manjunath; Manoj G Madakshira; Dipankar De; Sanjeev Handa; Debajyoti Chatterjee; Bishan D Radotra (Wolters Kluwer Medknow Publications, 2022)
Background: Currently, there is no cure for epidermolysis bullosa (EB) but few studies have explored the role of aminoglycosides in promoting collagen 7 expression in recessive dystrophic EB (RDEB). Materials and Methods: Consecutive patients aged >1 year with a confirmed diagnosis of dystrophic EB (DEB) were advised to apply 0.1% w/w gentamicin cream in a collagen base (Derbriment GTM) twice daily on a representative area on right lower limb (RLL) and paraffin gauze dressings on the corresponding opposite side on the left lower limb (LLL). Skin lesions were evaluated clinically during the 12-week treatment period at the end of which a repeat skin biopsy was sent for immunofluorescence antigen mapping (IFM). Results: Twelve patients with DEB were recruited but only eight completed the study and were analyzed. The mean fluorescence intensity (MFI) of the study cohort increased from 2765 ± 1732.07 (263-4845) at baseline to 5412.75 ± 3937.64 (2100-13536) at 12 weeks; a 95.75% (range 5.34%-775.14%) increase in the MFI of collagen 7 from baseline (P = 0.06). Among patients with a known termination codon mutation (n = 3), the percentage increase in MFI was greater among patients with known premature termination codon (PTC) mutations compared to those with unknown mutations. The clinical severity did not change significantly in terms of the mean number of blisters, erosions, and scarring during the study period. None of the parents reported any adverse effect. Conclusions: Topical gentamicin 0.1% w/w is a safe and effective way to promote the expression of COL7A1 in DEB patients, especially those carrying PTC mutations.